Respuesta :

Answer:

The sum of the expression (8 - 4i) + (-2 +7i) is (6 + 3i)

Step-by-step explanation:

In the complex numbers (a + bi) and (c + di), we can add the real parts together and the imaginary parts together, so their sum is

(a + bi) + (c + di) = (a + c) + (b + d)i

Let us use this fact to solve our question

∵ The complex numbers are (8 - 4i) and (-2 + 7i)

∴ Their sum = (8 - 4i) + (-2 + 7i)

∵ The real parts are 8 and -2

∵ 8 + -2 = 8 - 2 = 6

The sum of the real parts is 6

∵ The imaginary parts are -4i and 7i

∵ -4i + 7i = 3i

The sum of the the imaginary parts is 3i

∵ (8 - 4i) + (-2 + 7i) = (8 - 2) + (-4 + 7)i

∴ (8 - 4i) + (-2 + 7i) = 6 + 3i

The sum of the expression (8 - 4i) + (-2 +7i) is (6 + 3i)

ACCESS MORE